Hubungan Kesehjateraan Guru Terhadap Kinerja Guru Madrasah Aliyah Swasta Persiapan Negeri Besitang Kabupaten Langkat - Alfansuri, Dite Umbara; Rais, Muhammad Rijali (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the relationship between teacher welfare and teacher performance at Madrasah Aliyah Persiapan Negeri (MAPN) Besitang, Langkat Regency. This study uses a quantitative approach with a correlational method. The population in this study were all teachers at MAPN Besitang, totalling 23 people, as well as the research sample through the saturated sample technique. The instrument used to measure both variables is a Likert scale questionnaire that has been tested for validity and reliability. The data collection technique was carried out through distributing questionnaires directly to all respondents. The collected data were analysed using descriptive and inferential statistical techniques, namely Pearson Product Moment correlation analysis. The results showed that there is a significant relationship between teacher welfare and teacher performance, with a correlation coefficient of 0.722 at the 5% significance level. This means that the higher the level of teacher welfare, the higher the teacher performance, and vice versa. The coefficient of determination of 0.521 indicates that 52.1% of the variation in teacher performance can be explained by the teacher welfare variable, while the rest is influenced by other factors outside this study. Thus, teacher welfare is an important factor that contributes to improving teacher performance at MAPN Besitang.